Transcatheter device closure of atrial septal defect in dextrocardia with situs inversus totalis - Acharya, Kiran Prasad; Adhikari, Chandra Mani; Khanal, Aarjan; Dhungel, Sachin; Bogati, Amrit; Shrestha, Manish; Sharma, Deewakar (Nepalese Heart Journal, 2019)
Only few cases of Device closure of atrial septal defect in dextrocardia with situs inversus totalis has been reported previously. We present a case of a 36 years old male, who had secundum type of atrial septal defect in dextrocardia with situs inversus totalis. ASD device closure was successfully done. However, we encountered few technical difficulties in this case which are discussed in this case review.